HUBUNGAN PERSEPSI PENERAPAN FUNGSI KELUARGA DENGAN PERNIKAHAN DINI PADA WANITA USIA SUBUR DI KECAMATAN PRACIMANTORO, KABUPATEN WONOGIRI TAHUN 2016 - Audina, Alfin; Winarni, Sri; Dharminto, Dharminto; Mawarni, Atik (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
District Pracimantoro in 2016 there are 418 marriages with 66.50% is the case of early marriage. The Government of Indonesia through BKKBN has developed a Generasi Berencana (GenRe) program to reduce early marriage rates. One of the substance of GenRe program is 8 family functions. The purpose of this study to determine the relationship between perceptions about family functions implementation with early marriage in women childbearing age in District Pracimantoro, Wonogiri regency in 2016. The research type is quantitative with cross sectional design. The population are women childbearing age who recorded in KUA Pracimantoro Sub-district in 2016 with total 418 people. Sample are 80 people selected by proportional random sampling. The result shows that respondent's perception about reproduction function implementation is categorized less (53.8%), perception about economic function implementation is categorized less (53.8%) and perception about protection function implementation is categorized good (52.5%). Early marriage was more common in respondents with perceptions of less reproduction function (55.8%), perception of less economic function (58.1%) and perception of less protection function (68.4%). There is a relation between perceptions about protection function implementattion (p value = 0.004) and there is no correlation between perceptions of reproductive function implementation (p value = 0.370) as well as the perception of economic function implementation (p value = 0.178) with the early marriage (chisquare continuity correction test). Parents need continuously to provide information about the importance of family functions to children for example when family gatherings or meals together with the risk of early marriage.